Bargaining with Many Players: A Limit Result - Klaus Kultti; Hannu Vartiainen (Aboa Centre for Economics (ACE), 2008)
We provide a simple characterization of the stationary subgame perfect equilibrium of an alternating offers bargaining game when the number of players increases without a limit. Core convergence literature is emulated by increasing the number of players by replication. The limit allocation is interpreted in terms of Walrasian market for being the first proposer.
Keywords: C72; C78; 330; non-cooperative bargaining; stationary equilibrium; replication; Walrasian market